MONITORING SYSTEM ON VILLAGE FUND: SYNERGY BETWEEN COMMUNITIES AND REGULATORS (CASE STUDY ON BOGOR DISTRICT GOVERNMENT) - Rochman Marota; Asep Alipudin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The Village Law gives new meaning to trust by viewing the village as an institution equal to the regional government. Not only as an institution providing letters or government accomplices but an institution that independently and has the task of maintaining the welfare of the small unit in the community. These consequences provide a view of the professionalism of performance that can be monitored transparently and accountably. The urgency of this research lies in its objectives and benefits for the government and village officials, namely to provide a complete and factual picture of the system of monitoring on village funds from all aspects of development, management, accountability, and evaluation as well as strengthening the capabilities of village officials in managing funds and overseeing programs funded specifically by village funds and village development in general. This study concludes that there is a relationship between the stages of development, management and financial accountability starting from the process of planning, implementing, administering and reporting village funds to the monitoring system. The expected managerial implication is the synergy in the supervision of village funds between the ministry's regulators and the community, sub-district heads, Village Consultative Body, Government Internal Control Apparatus, Audit Board of the Republic of Indonesia, and Corruption Eradication Commission to optimize transparent and accountable monitoring.